2020
DOI: 10.1177/1477760620977500
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanical properties of concrete containing recycled aggregate and scrap crumb rubber and polypropylene fibers

Abstract: In this study, the effect of using crumb rubber and recycled aggregates on the mechanical properties of concrete has been evaluated as areplacement of fine and coarse aggregates In order to add the admixtures and evaluate their combined effect, 20 different types of concrete mixture ratio were prepared. The results indicated that in those samples containing crumb rubber and recycled aggregates the compressive strength is reduced and adding fiber up to 0.1%. to these concrete samples can improve the compressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A high-performance water-reducer agent used is Q8011 polycarboxylic acid-based (standard type) water reducer produced by QinFen Building Materials Factory, with a water reduction rate of 26%, as shown in Figure 2(a). Rubber aggregate used in the experiment is 40mesh rubber powder with an apparent density of 1.05 g/cm 3 produced by Sichuan Sito Rubber Co., Ltd, as shown in Figure 2(b). The sand is ordinary river sand, with an apparent density of 2.793 g/ cm 3 determined by the drainage method and a fineness modulus of 2.43.…”
Section: Test Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…A high-performance water-reducer agent used is Q8011 polycarboxylic acid-based (standard type) water reducer produced by QinFen Building Materials Factory, with a water reduction rate of 26%, as shown in Figure 2(a). Rubber aggregate used in the experiment is 40mesh rubber powder with an apparent density of 1.05 g/cm 3 produced by Sichuan Sito Rubber Co., Ltd, as shown in Figure 2(b). The sand is ordinary river sand, with an apparent density of 2.793 g/ cm 3 determined by the drainage method and a fineness modulus of 2.43.…”
Section: Test Materialsmentioning
confidence: 99%
“…Rubber aggregate used in the experiment is 40mesh rubber powder with an apparent density of 1.05 g/cm 3 produced by Sichuan Sito Rubber Co., Ltd, as shown in Figure 2(b). The sand is ordinary river sand, with an apparent density of 2.793 g/ cm 3 determined by the drainage method and a fineness modulus of 2.43. Rubber powder was added to replace part of the fine aggregate by equal volume ratio.…”
Section: Test Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although higher rubber content could lead a reduction in the mechanical performance of concrete, the negative effects can be mitigated by judiciously adding steel fibres and silica fume, which have a positive influence on its microscopic interface [23][24][25][26]. Zahid and Moein [27,28], in their study on the mechanical properties of recycled aggregate concrete containing crumb rubber, found that flexural strength decreased with CR content increases, with a combination of 5% CR and 2% volume of fibres yielding the highest toughness and ductility. Shahjalal, et al [29] observed that a mixture of 5% CR and fibres enhanced energy absorption capability, when toughness and ductility gradually decreased with increasing CR content.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Today, the aim is to evaluate recycled rubber particles in concrete, with many studies aimed at developing rubberized concrete. [9][10][11][12][13] These rubber particles are used in three classes: chips, crumbs, and powder rubber. 14 Waste rubbers can be commercialized and used in asphalt, plaster, mortar, and concrete.…”
Section: Introductionmentioning
confidence: 99%